Bioluminescent Antibodies for Point‐of‐Care Diagnostics. Issue 25 (16th May 2017) - Xue, Lin; Yu, Qiuliyang; Griss, Rudolf; Schena, Alberto; Johnsson, Kai
Abstract: We introduce a general method to transform antibodies into ratiometric, bioluminescent sensor proteins for the no‐wash quantification of analytes. Our approach is based on the genetic fusion of antibody fragments to NanoLuc luciferase and SNAP‐tag, the latter being labeled with a synthetic fluorescent competitor of the antigen. Binding of the antigen, here synthetic drugs, by the sensor displaces the tethered fluorescent competitor from the antibody and disrupts bioluminescent resonance energy transfer (BRET) between the luciferase and fluorophore. The semisynthetic sensors display a tunable response range (submicromolar to submillimolar) and large dynamic range (Δ R max >500 %), and they permit the quantification of analytes through spotting of the samples onto paper followed by analysis with a digital camera. Abstract : Paper test : Ratiometric bioluminescent sensors with high selectivity, tunable response range, and a large dynamic range were developed based on antibodies. Moreover, when incorporated into paper‐based point‐of‐care devices, the antibody‐based sensors permit the rapid, reliable, and portable quantification of analytes in serum and blood samples using a digital camera.